Clinical manifestations and outcomes of 420 children with Henoch Schönlein Purpura from a single referral center from Turkey: A three-year experience. Issue 6 (1st November 2020) - Ekinci, Rabia Miray Kisla; Balci, Sibel; Melek, Engin; Karabay Bayazit, Aysun; Dogruel, Dilek; Altintas, Derya Ufuk; Yilmaz, Mustafa
Abstract: Objectives: Henoch Schönlein Purpura (HSP) is the most common systemic vasculitis in childhood. We aimed to evaluate the clinical features, seasonal variation, treatment outcomes and the possible predicting factors related to outcome among a large cohort of pediatric HSP patients. Methods: We conducted a medical record review study between July 2016 and January 2019 and evaluated the clinical manifestations and potential risk factors for severe gastrointestinal (GI) involvement, biopsy-proven nephritis and relapses. Results: The study included 420 HSP patients, of which the mean age at diagnosis was 7.68 ± 3.15 years. Clinical manifestations were arthralgia and/or arthritis ( n  = 244, 58.1%), abdominal pain ( n  = 235, 56%), subcutaneous edema ( n  = 163, 38.8%), and renal involvement ( n  = 125, 29.8%). Disease recurred for at least once, in 69 (16.4%) patients and colchicine treatment yielded a favorable response in 11 of 12 relapsing patients, who did not respond to ibuprofen or steroids. Frequencies of renal involvement and biopsy-proven nephritis were higher in patients with severe GI involvement. Besides, patients with biopsy-proven nephritis had higher rates of abdominal pain, intussusception, severe GI involvement, and systemic steroid administration. Conclusion: We speculate that renal involvement, biopsy-proven nephritis and severe GI involvement can be related to each other. Colchicine may be effective in patients with relapsing disease.